High Frequency Oscillations in Rat Hippocampal Slices: Origin, Frequency Characteristics, and Spread - Naggar, Isaac; Stewart, Mark; Orman, Rena (Frontiers in Neurology, 2020)
Field potential oscillations reflect repetitive firing and synaptic activity by ensembles of neurons in certain areas of the brain. They can be distinguished as slow (e.g., alpha, delta and theta), fast (e.g., beta and gamma) and high frequency oscillations (HFOs). Neuronal oscillations are involved in a variety of physiological and pathophysiological states such as cognition, consciousness and seizures. The laminar structure of rat hippocampus affords a way to study these oscillations in hippocampal slices. Rat ventral hippocampal brain slices were cut and maintained in a recording chamber that permitted 64 simultaneous extracellular recordings in the presence of artificial CSF. Brief single stimulus pulses were applied with bipolar electrodes to the CA3 or CA1 regions of hippocampus. Single pulses triggered epileptiform population events that included HFOs in the 150-250 Hz range in the presence of GABAA receptor blockade or kainic acid. HFOs also occurred spontaneously in the presence of kainic acid. The oscillations had the largest amplitude in the CA3c cell layer, regardless of the drug, and were synchronized throughout the cell layer. AMPA receptor blockade stopped these HFOs, whereas NMDA receptor blockade did not. Gap junction activation did not restore HFOs in the presence of AMPA receptor blockade. Our findings suggest that a population of excitatory neurons in CA3c may be a primary focus of seizure-like activity in Ammon’s Horn. We suggest that the interconnection of CA3c is different from the rest of CA3.